The Role of Traditional Home Gardens in Cultural Rituals and Heritage Preservation: An Ethnobotanical Study in Pujon Sub-district, Malang Regency, Indonesia - Agustina, Tika Putri; Rukmana, Musma; Hasmiati, Hasmiati; Kawuwung, Femmy Rose (Universitas Sultan Ageng Tirtayasa, 2025)
This study explores the critical role of home gardens in traditional rituals in Pujon District, Malang Regency. Sustained by long standing customs, home gardens are significant social, cultural, and economic importance, especially concerning local customs. The research aims to identify the plant species cultivated in these gardens, their functions in ritual ceremonies. Adopting a qualittaive researched framework this study utilized a descriptive approach involving field observations and in-depth interviews. Key informants, incorporating garden owners, customary elders, and community leaders, were purposively selected. The results show that home gardens in Pujon Sub-district function as crucial green spaces and sources of food while also serving as focal points for social and cultural activities. Plants such as banana (Musa x paradisiaca), coconut (Cocos nucifera), jasmine (Jasminum sambac), and rose (Rosa sp.) are necessary to numerous ceremonies and traditional rituals. The preservation of knowledge regarding these plants is maintained through storytelling and daily activities, highlighting their role in sustaining local culture and biodiversity. As a result, home gardens play a crucial role in encouraging cultural identity and ecological balance in the region.